Decision Support System For Selection Of Student Competition Supervisor at Dinamika University - Herwanda Ayu Destania; Rochmat Rizky Alfandy; Muhammad Wahyudi; Julianto Lemantara (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Every university in Indonesia has the right to take part in any competition from Directorate General of Learning and Student Affairs (Belmawa) by sending several teams consisting of students and supervisors. After doing observations, there were 83% of 35 students who took part in Belmawa competition at Dinamika University had difficulty in choosing a supervisor. The causes students choose a supervisor at random. When the students conducting guidance does not match the profile of the selected supervisor and the guidance results are not optimal. Therefore, this study aims to produce an Decision Support System (DSS) for determining the best supervisor of Belmawa competition using Analytical Hierarchy Process (AHP) and Graphic Rating Scale (GRS) methods to improve quality in choosing the supervisor for Belmawa competition. In its application, AHP was used to generate local priority from each criterion and GRS was used for ranking of each lecturer and then 4 lecturers with the highest score were selected. The results showed DSS could assist students in selecting prospective supervisors according to the existing criteria, namely: the supervisor's last education level, the number of publications from supervisor, the type of supervisor's expertise, the number of teams that asked for guidance, and the number of belmawa competitions, which has been achieved by students under the guidance of supervisor. This was evidenced by the decrease in the difficulty of selecting Belmawa supervisors at Dinamika University from 83% to 5.71%